The Influence of Inquiry Learning Model on Grade X Students Biology Learning Outcomes in Ecosystem Material - Yulita, Nourma; Fadila, Candra Ardan; Syam, Andi Nurannisa (IAIN Kendari, 2024)
The present study aims to: 1) interpret the influence of the inquiry learning model on students' biology learning outcomes; 2) interpret the implementation of each stage of the inquiry learning model. The present study is quantitative research using a quasi-experimental design, which was carried out at SMA Negeri 2 South Konawe. The research samples were grade X MIPA1 students as the experimental class and grade X MIPA3 students as the control class. The data collection technique for this research is tests that were analyzed descriptively and inferentially, as well as observations to interpret the implementation of the inquiry learning model. The results show that: 1) the inquiry learning model has a positive effect on the biology learning outcomes of grade X students on the ecosystem material. The inquiry learning model has an effective effect of 74.82% in learning activities and 25.18% is influenced by other variables which are not examined in this research, so the model is categorized as quite effective; 2) the inquiry learning model applied to grade X ecosystem material has difficulties in learning activities, namely difficulties in orienting the material and formulating problems. The biggest difficulty faced by the teacher is collecting data and drawing conclusions, which is caused by the teacher’s lack of ability to organize the learning time.